Personal resources for addressing the work demands of Ukrainian oncologists in stressful crisis situations - I Böckelmann; I Zavgorodnii; O Litovchenko; V Kapustnyk; M Krasnoselskyi; Beatrice Thielmann (BMC, 2024)
Abstract Background Many work-related stresses are experienced by oncologists. Ukraine is currently undergoing numerous crises, including the SARS-CoV-2 pandemic and military conflicts, which represent stressful situations. The aim of this study was to explore the personal resources that Ukrainian oncologists use to cope with work demands in a situation featuring manifold crises. This study identified the ways in which people deal with stressful situations and the roles that they play in shaping the challenging situations that they encounter (work-related behavior) as well as how they cope with stress (stress management). Methods Forty oncologists (18 men and 22 women) working in a clinic in Kharkiv (Ukraine) with an average age of 46.3 ± 13.37 years (ranging from 26 to 74 years) participated in this study. The occupational psychological survey consisted of the Work-Related Behavior and Experience Patterns (German: Arbeitsbezogenes Verhaltens- und Erlebensmuster, AVEM) questionnaire, which was developed by Schaarschmidt and Fischer, and the Differential Stress Inventory (DSI), which was developed by Léfevre and Kubinger. Results 65% of oncologists exhibited AVEM risk pattern A or B. No gender differences were observed with regard to the distribution of AVEM patterns. Women obtained significantly higher scores than did men on only one dimension: experience of social support (4.86 vs. 3.44; p = 0.045). When the DSI categories were differentiated by gender, no significant differences were observed. Spearman's correlation analysis revealed a medium-sized correlation between perfection striving and palliative coping (ρ = 0.404). Conclusions Few gender-based differences in work-related behaviors, experiences, and stress management strategies are evident among oncologists. AVEM risk patterns are more prevalent among Ukrainian oncologists than among comparable occupational groups, and interventions in the context of health management are recommended.